E-Court Daiam Penerapan Prinsip Peradilan Sederhana, Cepat Dan Biaya Ringan Di Pengadilan Negeri Tuban - Mustafa Ashari (Widya Yuridika, 2022)
After the spread of the COVID-19 virus pandemic, government administrative services began to be shifted to electronic media. The court service is no exception. One of the services that are present in the community is E-Court. This study aims to find out how the implementation of E-Court in applying the principles of justice which is simple, fast and low cost and to find out what are the obstacles of E-Court in implementing the principles of justice which are simple, fast and low cost in the Tuban District Court. This study using empirical juridical research methods with primary data sources and secondary data. Primary data is data that comes from the original or first source by conducting interviews with related parties while secondary data is some data obtained through libraries which include books and documents, related to the object of research. Data collection methods used are field observations, interviews with resource persons and literature studies with qualitative analysis data analysis techniques. The results of this study are the implementation of E-Court at the Tuban District Court can apply a simple, fast and low-cost trial as well as several obstacles encountered, including the unprepared human resources in Tuban district, signal strength and internet networks that are not evenly distributed in each sub-district. in Tuban district, the E-Court server is slow during peak hours, E-Payment is not yet integrated with all banks, and finally E-Court in its implementation still relies on the principle of consensuality.